INTERNALIZATION OF NATIONAL CHARACTER VALUES THROUGH CIVICS EDUCATION: A STUDENT PHENOMENOLOGICAL STUDY - Warsito (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This study aims to describe students’ experiences in internalizing national character values through Civic Education courses and to analyze the extent of their implementation in campus life. This research employed a qualitative approach using a phenomenological method to explore students’ lived experiences. The participants consisted of six second-semester students enrolled in the Civic Education course at STABN Sriwijaya Tangerang. Data were collected through in-depth interviews, observations, and documentation, while data analysis followed Creswell’s phenomenological model. The results indicate that students internalize various national character values, including religiosity, honesty, tolerance, discipline, hard work, independence, democratic attitudes, and responsibility. These values are reflected in both academic and social activities, although the level of implementation varies among individuals. The findings also reveal that the role of lecturers, learning environment, and instructional strategies significantly influence the internalization process. Furthermore, Civic Education courses play a strategic role in shaping students’ character as responsible and active citizens. However, the inconsistency in value implementation suggests the need for more systematic and practice-based learning approaches.